Nilai Karakter yang Terkandung dalam Buku Cerita Bergambar Karya Dini W. Tamam - Bagus Faizal Rizal; Tanzil Huda; Agus Milu Susetyo (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
A study cannot be separated from the problem that needs to be explained. The problem that arises from the background is how are the character values ​​contained in picture story books? The purpose of this study is to describe the character values ​​contained in picture story books. This type of research is qualitative. The object studied to be described is the character values ​​contained in picture story books by Dini W. Tamam. The data in this study are in the form of sentences or paragraphs containing character education values. The data were collected through documentation and analyzed with the following steps: (1) data grouping, (2) data coding, (3) inference, (4) analysis. The main tool for collecting data is a table and the researcher as the main instrument. The results of the data analysis show that the book "The Most Exciting Collection of Character-Building Tales" has a variety of very relevant character values, such as religious, honest, tolerant, disciplined, hard work, creative, independent, democratic, appreciating achievement, friendly, loving peace, caring for society, and responsible. It is important to start character education early on, especially in the family environment. This book is very suitable for children under 10 years old because it contains fictional stories that carry valuable character education values ​​for their future. Based on these results, the conclusion of this study is that the children's story book entitled "The Most Exciting Collection of Character-Building Tales" contains stories that are appropriate for children under 10 years old. This is because the book is proven to contain fictional stories that contain character education values. These character values ​​are useful for the future.